Obus : A Two-Dimensional (2D) Game Preserving Bidayuh Folklore and Symbolism - Abby Lian, Hendrick; Suriati Khartini, Jali; Mohamad Imran, Bandan; Nurfauza, Jali; Lim, Phei Chin; Aliffazraie, Jali; Sarni Suhaila, Rahim; Sylvester, Arnab (Semarak Ilmu Publishing, 2026)
Digital games have the potential to preserve cultural heritage, including the fading traditions of Bidayuh folklore and symbolism. This project aims to develop a 2D game that digitally adapts Bidayuh traditions, providing a modernised way to transmit this cultural knowledge. A 2D HTML game prototype titled Obus was designed and developed. The prototype was hosted on Itch.io for online testing and a separate executable file was distributed for offline testing. Distributed questionnaires consisted of open-ended and close-ended questions based on the Technology Acceptance Model (TAM). Responses were collected online and using non-probability sampling techniques. The study involved 33 participants across Malaysia, and their feedback was analysed to determine the feasibility of using game-based learning for cultural preservation. Perceived usefulness achieved a Cronbach’s alpha value of 0.74012 while perceived ease of use scored 0.54606. Overall, the System Usability Scale (SUS) results were encouraging (mean=72.27, SD=12.54, n=33), suggesting that the implementation of digital games was perceived as useful and usable. The findings indicated its potential as an engaging and educational tool for preserving Bidayuh heritage while needing to focus on ease of use.